Advance in Energy Harvesters/Nanogenerators and Self-Powered Sensors - Shi, Qiongfeng; Zhu, Jianxiong (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a collection of the Special Issue "Advance in Energy Harvesters/Nanogenerators and Self-Powered Sensors" published in Nanomaterials, which includes one editorial, six novel research articles and four review articles, showcasing the very recent advances in energy-harvesting and self-powered sensing technologies. With its broad coverage of innovations in transducing/sensing mechanisms, material and structural designs, system integration and applications, as well as the timely reviews of the progress in energy harvesting and self-powered sensing technologies, this reprint could give readers an excellent overview of the challenges, opportunities, advancements and development trends of this rapidly evolving field.